Iron-bearing minerals in clays related to the Holocene marine ingression in the coastal plain of the Río de la Plata estuary (Argentina): paleoenvironmental implications (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Iron in sediments can be part of a wide variety of minerals which characteristics are heavily dependent upon the environmental conditions. Hence, their knowledge is useful for paleoenvironmental inter pretations. The aim of this work is to contribute to the understanding of ironbearing minerals in clay deposits associated whit the Holocene hypsthermal sealevel fall, in the coastal plain of the Río de la Plata estuary, at Ensenada, Berisso and La Plata localities (Figs. 1, 2a). The studied unit corresponds to the Villa Elisa Facies of the Las Escobas Formation (Cavallotto, 1995 , Fig. 2b). The aforementioned author indicated that the analyzed deposits reflected sedimentation in a marinecontinental transition linked to a saltmarsh environment, developed when the Holocene sea flooded the coastal plain. Cavallotto (1995) also indicated that this lowenergy environment would have received suspended material from different origins (such as creeks and tidal currents), which flocculated as result of a high salinity. An important aspect to emphasize is that these deposits comprise the parent materials of the soils of the region that has been classified as Vertisols (see Imbellone and Mormeneo, 2011). The present study includes the use of several techniques of proven effectiveness for mineralogical characterization, especially related to ironbearing minerals in order to contribute to the paleoenvironmental interpretation of this unit. In addition, the results allow performing inferences that may interest to Soil and Environmental Sciences. Sampling was performed in eight excavations (Figs. 2a, 3) where eleven samples were obtained at depths ranging from 20 to 110 cm. The most affected levels by the current pedogenetic cycle (A horizons) were not taken into account. Routine analyses such as color, grain size, organic matter and swelling were performed (Table 1), in addition to chemical analysis (Table 2), Mössbauer spectroscopy (Fig. 4; Table 3), magnetic properties (Figs. 6, 7; Table 4,), Xray diffraction (Fig. 8; Table 5) and differential thermalthermogravimetric ana lysis (Fig. 9). The analyzed samples are grayolive in color (commonly known in Soil Science as gley colors) and show a clear predominance of clay fraction. From a textural point of view, the materials are classified as clays (Fig. 4). Samples are composed of a mineralogical complex association, although considering the wide area of sampling, the composition (e.g., texture, magnetic parameters, chemical elements) are similar in all samples. This association results from the combination of multiple factors, including processes related to the source area, the depositional environment at a saltmarsh, and also the current pedogenetic environment. The clay minerals (approximately 60% of total) are dominant over the other mineral phases, represented mainly by smectites and illite, and secondarily by kaolinite and interstratified I/S (Table 5; Fig. 8). Also quartz, plagioclase, alkaline feldspar, and to a lesser extent calcite and iron oxyhydroxides (goethite and probably ferrihydrite), are present. The presence of goethite is consistent with the magnetic and differential thermalthermogravimetric results (Table 4; Figs. 6, 9), which also evidenced a low concentration of this mineral (less than 3%). Samples have shown a considerable total iron content (about 10%; Table 2) and according to the Mössbauer spectroscopy the ferric iron (Fe3+) predominates over the ferrous (Fe2+), being the relative percent of Fe3+ phase approximately 92% and Fe2+ phase only around 8% (Table 3; Fig. 5). In view of these results the iron oxyhydroxides do not constitute a dominant mineral phase, and therefore do not represent the main ironbearing minerals. On the basis of the obtained results, it is concluded that Fe3+ is mainly within the clay minerals structure, in particular in ironrich smectites, of the nontronite/Febeidellite type. The mineral association presented here has important implications for paleoenvironmental inter pretations. Taking into account the previous mo dels that considered the Villa Elisa saltmarshes Facies of Las Escobas Formation, we concluded that this environment received clay minerals, coming from the erosion of loessic soils (mainly smectites and illite) in addition to a tidal input (more rich in smectites and kaolinite). Once deposited, those materials were subjected to the environmental con ditions, including repeated wettingdrying cycles and their respective Eh fluctuations under slightly alkaline pH conditions. Such conditions gave rise to complex mechanisms, which allowed the incor poration of iron into the smectites structure. One interesting aspect to emphasize is that the gley colors of these materials were originated by Fe3+ bearing minerals as Fesmectites, which contradicts the traditional assignation of this color pattern to Fe2+ iron minerals. Besides, it is highlighted that the participation of Fesmectites in association with iron oxyhydroxides, contributes to the adsorption of heavy metals and other contaminants of the region. This aspect gives to the Villa Elisa Facies a great environmental importance.
Keywords: Fesmectites, Goethite, Saltmarsh, Verti sol, Earth´s Critical Zone, Argentina